1996
DOI: 10.1128/jvi.70.1.1-9.1996
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the murine AIDS defective virus does not encode a superantigen

Abstract: The T-cell receptor repertoire was analyzed in C57BL/6 mice upon infection with helper-free stocks of the pathogenic murine AIDS (MAIDS) defective virus in order to demonstrate if, as previously reported, this virus encodes a superantigen. A polyclonal T-cell stimulation involving T cells expressing multiple V␤ subsets occurred within the first week of infection, while late in the disease we could note only a 50% deletion of V␤5 CD8 ؉ cells. Transfection of the MAIDS virus genomic DNA into fibroblasts and B ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…We next studied whether c-Abl associates with Pr60 gag in vivo, by coimmunoprecipitation. We used a nonproducer B-cell line (CST-B5) established from a MAIDS virus-infected mouse (10), in which Pr60 gag could be overexpressed. We isolated two clones (SB19 and SB21) which overexpressed Pr60 gag at levels 10-to 15-fold higher than those produced by the parental CST-B5 cells (Fig.…”
Section: Maids-binding Site For Sh3 [Mb3-1] [Lipskppksr] Mb3-2 [Enlpmentioning
confidence: 99%
“…We next studied whether c-Abl associates with Pr60 gag in vivo, by coimmunoprecipitation. We used a nonproducer B-cell line (CST-B5) established from a MAIDS virus-infected mouse (10), in which Pr60 gag could be overexpressed. We isolated two clones (SB19 and SB21) which overexpressed Pr60 gag at levels 10-to 15-fold higher than those produced by the parental CST-B5 cells (Fig.…”
Section: Maids-binding Site For Sh3 [Mb3-1] [Lipskppksr] Mb3-2 [Enlpmentioning
confidence: 99%
“…In addition, both this report and several others (Hugin et. al, 1991;Muralidhar et al, 1992;Gilmore at al., 1993;McCarty et al, 1996;Doyon et al, 1996;Hayashi and Kanagawa, 1999) have argued against the presence of a SAg in MAIDS, particularly the one proposed early on as expressed on a terminal B-cell lymphoma line from a B6 mouse with end-stage MAIDS (Hugin at al., 1991).…”
Section: Discussionmentioning
confidence: 99%
“…If TCR is indeed engaged, then it would follow that a viral peptide, induced self peptide, or superantigen (SAg) complexed with MHC class II would be the TCR ligand driving Signal 1 propagation. However, as no LP-BM5 virusencoded or -associated peptide, or SAg, has yet been defined that could provide the ligand for the CD4 TCR in the context of MAIDS (Hugin et al, 1991;Muralidhar et al, 1992;Gilmore at al., 1993;McCarty et al, 1996;Doyon et al, 1996;Hayashi and Kanagawa, 1999), the question of a requirement for CD4 TCR engagement in MAIDS can not be approached using antibody or other reagents to block the ligation of the TCR by these putative peptide or SAg -MHC complexes. Also, it is not possible to study the need for the TCR by use of TCR -/mice because the required CD4 T cells will not be present.…”
Section: Introductionmentioning
confidence: 99%
“…Since it is unlikely that the viral genome encodes conventional superantigens [12,16] or other antigens responsible for the polyclonal activation of T-and B-cells, and since the T-cell dysfunction involves both naive and memory CD4 + T-cells [17], antigenindependent mechanisms may be crucial in the pathogenesis. We have recently reported that the intracellular level of cAMP is strongly increased in T-cells from MAIDS mice leading to constitutive activation of PKA (protein kinase A) type I [18].…”
Section: Introductionmentioning
confidence: 99%